Pemanfaatan Media Sosial Dalam Mengembangkan Perilaku Di Smk Negeri 2 Batam Provinsi Kepulauan Riau - Vip Tafuji Nandha; Rusmini Rusmini; Yusria Yusria (Universitas Pakuan, 2026)
THE UTILIZATION OF SOCIAL MEDIA IN DEVELOPING STUDENT BEHAVIOR AT SMK NEGERI 2 BATAM, RIAU ISLANDS PROVINCE This study aims to analyze the utilization of social media in developing students’ behavior and to identify the inhibiting factors and solutions implemented by schools in directing positive social media use within the educational environment. The research problem is based on the increasing use of social media among students which brings both positive and negative impacts on students’ social behavior. This research employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving vice principals, teachers, and students as research informants. The findings reveal that social media utilization has been directed through digital literacy programs, educational content creation training, and the integration of social media as a supporting learning medium. The inhibiting factors include exposure to negative content, digital trend influence, the Fear of Missing Out (FOMO) phenomenon, and limited supervision of students’ social media use. The solutions implemented by the school include strengthening digital literacy education, promoting ethical social media use, integrating technology into learning activities, and establishing collaboration between schools and parents in supervising students’ social media usage. Therefore, social media can contribute positively to students’ behavioral development when utilized wisely, systematically, and supported by active collaboration between schools and families.